Influência do período de armazenamento na qualidade de sementes Jatropha curcas L. - Höring, Carla Franciele (2008)
The search for alternative fuels from natural oils has attracted great interest in this culture, and also by the seeds of Jatropha curcas nut. Thus, this study aimed to evaluate the influence of storage period in the quality of Jatropha curcas L. seeds. Seeds used were from Eldorado city localed in the State of Mato Grosso do Sul Seeds were harvested and benefited manually and selected in accordance with the storage time in uncontrolled environment. The storage periods evaluated were 17, 40, 66, 108 and 164 days. Seeds were brought to the laboratory of Technology Seeds and Seedlings of the Universidade Estadual do Oeste do Paraná - UNIOESTE, Campus Marechal Cândido Rondon. There were measured humidity degree, thousand seeds, weight, single mass, diameter and length of the seed. Moreover, it was germination test and tetrazolium test. In the germination test it was evaluated the seeds performance in substrates of sand and paper in temperatures of 25±2°C and 30±2°C of each storage time and it was estimated the germination speed rate. The methodology of the test tetrazolium in the concentration of 0.1% was used to check the damage seeds. The germination of seeds was considered since the issuance of the radicle to the substrate paper and seedling immersed in the sand. In the methodology of the tetrazolium test the husk has been removed to facilitate the staining of seed. For storeg periods of Jatropha curcas seed, as longer is the storage time higher is the mass loss of the seeds. Seeds harvestd and store for up to 40 days have viability higher than those stored for 66 days to 164 days. The tetrazolium test probed to be satisfactory for observation the force and the viability of seeds, because it has a positive correlation with the germination test